A retrospective cohort study of predictors and interventions that influence cooperation with mask induction in children. Issue 8 (25th June 2020) - Marquez, Juan L.; Wang, Ellen; Rodriguez, Samuel T.; O'Connell, Chloe; Munshey, Farrukh; Darling, Curtis; Tsui, Ban; Caruso, Joseph; Caruso, Thomas J.
Abstract: Background: Uncooperative pediatric mask induction is linked to perioperative anxiety. Although some risk factors for uncooperative inductions have been reported, there are no large cohort studies that identify intrinsic patient characteristics associated with cooperation. Aim: The primary aim was to identify patient characteristics associated with cooperative mask inductions. The secondary aim was to determine whether preoperative interventions were associated with increased cooperation. Methods: This retrospective cohort study included patients 2‐11 years old and ASA class I‐IV who underwent mask induction. Our primary outcome of interest was cooperation with mask induction, which was correlated against the Induction Compliance Checklist. The variables analyzed for association with cooperation were age, sex, ASA class, class of surgery, preferred language, and race. Interventions examined for association with induction cooperation included premedication with midazolam, exposure to distraction technology, parental presence, and the presence of a Child Life Specialist. Multivariate mixed‐effects logistic regression was used to assess the relationship between patient characteristics and cooperation. A separate multivariate mixed‐effects logistic regression was used to examine the association between preoperative interventions and cooperation. Results: 9692 patients underwent 23 474 procedures during the study period. 3372 patients undergoing 5980 procedures met inclusion criteria. The only patient characteristic associated with increased cooperation was age (OR 1.20, p‐value 0.03). Involvement of Child Life Specialists was associated with increased cooperation (OR 4.44, p‐value = 0.048) while parental/guardian presence was associated with decreased cooperation (OR 0.38, p‐value = 0.002). Conclusion: In this cohort, increasing age was the only patient characteristic found to be associated with increased cooperation with mask induction. Preoperative intervention by a Child Life Specialists was the sole intervention associated with improved cooperation.